Association between Temporomandibular Joint Disorder and Parkinson’s Disease - Hyo-Geun Choi; Joo-Heung Yoon; Tae-Hwan Chung; Chanyang Min; Dae-Myoung Yoo; Jee-Hye Wee; Suk-Yun Kang; Yeso Choi; Seok-Jin Hong; Soo-Hwan Byun (Brain Sciences, 2021)
This study performed two different analyses using a large set of population data from the Korean National Health Insurance Service Health Screening Cohort to evaluate the interactional association between temporomandibular disorder (TMD) and Parkinson’s disease (PD). Two nested case–control population-based studies were conducted on 514,866 participants. In Study I, 4455 participants with TMD were matched with 17,820 control participants, with a ratio of 1:4. In Study II, 6076 participants with PD were matched with 24,304 control participants, with a ratio of 1:4. Obesity, smoking, alcohol consumption, systolic, diastolic blood pressure, fasting blood glucose level, and total cholesterol were adjusted. The adjusted odds ratio (OR) for TMD was 1.43 (95% confidence interval (CI) = 1.02–2.00) in PD patients compared to non-PD patients in Study I (p < 0.001). The adjusted OR for PD was 1.56 (95% CI = 1.13–2.15) in TMD patients compared to non-TMD patients in Study II (p = 0.007). This study demonstrated that patients with TMD have a significantly higher risk of developing PD and, conversely, those with PD have a significantly higher risk of developing TMD.